Biochemical and Ultrastructural Changes in the Hepatopancreas of Bellamya aeruginosa (Gastropoda) Fed with Toxic Cyanobacteria. (1st November 2011) - Zhu, Jinyong; Lu, Kaihong; Zhang, Chunjing; Liang, Jingjing; Hu, Zhiyong
Abstract : This study was conducted to investigate ultrastructural alterations and biochemical responses in the hepatopancreas of the freshwater snail Bellamya aeruginosa after exposure to two treatments: toxic cyanobacterium ( Microcystis aeruginosa ) and toxic cyanobacterial cells mixed with a non-toxic green alga ( Scendesmus quadricauda ) for a period of 15 days of intoxication, followed by a 15-day detoxification period. The toxic algal suspension induced a very pronounced increase of the activities of acid phosphatases, alkaline phosphatases and glutathione S-transferases (ACP, ALP and GST) in the liver at the later stage of intoxication. During the depuration, enzymatic activity tended to return to the levels close to those in the control. The activity of GST displayed the most pronounced response among different algal suspensions. Severe cytoplasmic vacuolization, condensation and deformation of nucleus, dilation and myeloid-like in mitochondria, disruption of rough endoplasmic reticulum, proliferation of lysosome, telolysosomes and apoptotic body were observed in the tissues. All cellular organelles began recovery after the snails were transferred to the S. quadricauda. The occurrence of a large amount of activated lysosomes and heterolysosomes and augment in activity of detoxification enzyme GST might be an adaptive mechanism to eliminate or lessen cell damage caused by hepatotoxicity to B. aeruginosa .